Diagnosis and severity criteria for sinusoidal obstruction syndrome/veno-occlusive disease in pediatric patients: a new classification from the European society for blood and marrow transplantation - Corbacioglu, S; Carreras, E; Ansari, M; Balduzzi, A; Cesaro, S; Dalle, J-H; Dignan, F; Gibson, B; Guengoer, T; Gruhn, B; Lankester, A; Locatelli, F; et al. (Bone marrow transplantation, 2018)
The advances in hematopoietic cell transplantation (HCT) over the last decade have led to a transplant-related mortality below 15%. Hepatic sinusoidal obstruction syndrome/veno-occlusive disease (SOS/VOD) is a life-threatening complication of HCT that belongs to a group of diseases increasingly identified as transplant-related, systemic endothelial diseases. In most cases, SOS/VOD resolves within weeks; however, severe SOS/VOD results in multi-organ dysfunction/failure with a mortality rate >80%. A timely diagnosis of SOS/VOD is of critical importance, given the availability of therapeutic options with favorable tolerability. Current diagnostic criteria are used for adults and children. However, over the last decade it has become clear that SOS/VOD is significantly different between the age groups in terms of incidence, genetic predisposition, clinical presentation, prevention, treatment and outcome. Improved understanding of SOS/VOD and the availability of effective treatment questions the use of the Baltimore and Seattle criteria for diagnosing SOS/VOD in children. The aim of this position paper is to propose new diagnostic and severity criteria for SOS/VOD in children on behalf of the European Society for Blood and Marrow Transplantation.
Keywords: rizikové faktory; výsledek terapie; Hepatic Veno-Occlusive Disease; Evropa; Europe; Treatment Outcome; jaterní žilní okluze; Male; lidé; Female; mužské pohlaví; ženské pohlaví; Risk Factors; incidence; Incidence; Humans